MO942: Regulatory T and B Cell Responses are Equally Compromised During Antibody-Mediated Rejection of Kidney Allografts. (3rd May 2022) - Louis, Kevin; Fadakar, Paul; Macedo, Camila; Yamada, Masaki; Zeevi, Adriana; Randhawa, Parmjeet; Lefaucheur, Carmen; Metes, Diana
Abstract: BACKGROUND AND AIMS: Although considerable advances have been made in understanding the cellular effector mechanisms responsible for donor-specific antibody (DSA) generation leading to antibody-mediated rejection (ABMR), the identification of cellular regulators of such immune responses is lacking. METHOD: In a cohort of 96 kidney transplant recipients, we used high-dimensional flow cytometry to concomitantly profile and track the two major subsets of regulatory lymphocytes in the blood: T regulatory (TREG) and transitional B (TrB) cells. Additionally, we established co-culture assays to address their respective capacities to suppress antibody responses in vitro . RESULTS: TREG and TrB were potent suppressors of T follicular helper-mediated B cell differentiation into plasmablast and antibody generation. While TREG and TrB were both durably expanded in patients who did not develop DSA post-transplant, patients who manifested DSA and progressed to ABMR displayed a marked and persistent numerical reduction in TREG and TrB cells. Strikingly, specific cell clusters expressing the transcription factor T-bet were selectively depleted in both TREG and TrB compartments in patients with ABMR. Importantly, the coordinated loss of these T-bet + CXCR5+ TREG and T-bet+CD21–TrB cell clusters was correlated with increased and inflammatory DSA responses, more extensive microvascular inflammation and a higher rate of kidney allograft loss. CONCLUSION: Our study identified coordinated and persistent defects in the regulatory T and B cell responses in patients undergoing ABMR, which may contribute to their loss of humoral immune regulation and thus warranting timely therapeutic interventions to replenish and sustain TREG and TrB cells in these patients.